Defining Anxiety - Jusuf, Harni (Al-Lisan, 2015)
To support the successful of teaching learning process, it must be supported by some apsects, such as: learning syles, teaching strategies, affective factors, and socio-cultural factors. One of the affective factors that must be pay attention in language learning is anxiety. Usually, language anxiety happen when students learn foreign language. Anxiety divided into trait anxiety, state anxiety, and situation-specific anxiety. Language anxiety causes by three (1) communication apprehension (CA); (2) test anxiety; and (3) fear of negative evaluation. To know the level of studentsâ language anxiety, it can be measured through foreign language classroom anxiety scale (FLCAS). It is an instrument that has beendesigned firstly by Elaine K. Horwitz et al. The instrument is a questionnaireconsists of 33 item of questions.